2022
DOI: 10.1021/acs.jpcc.2c04707
|View full text |Cite
|
Sign up to set email alerts
|

Switchable Dielectric Two-Dimensional Lead-Free Perovskite with Reversible Thermochromic Response

Abstract: Two-dimensional (2D) organic–inorganic hybrid perovskites (OIHPs) have attracted great interest due to their unique properties for optical, thermal, electric, force, and magnetic applications. However, although some 2D HOIPs with thermochromic properties have been obtained, the issue of toxicity of lead and single-stimulus response impose restrictions on their further applications. To overcome this limitation, we scientifically design and fabricate a novel two-dimensional organic–inorganic hybrid lead-free per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 66 publications
0
20
0
Order By: Relevance
“…Moreover, the single crystal of 1 shows the thermochromic property that is similar to the other Cu II Cl complexes. ,,, As shown in Figure S14, the yellow single crystal at the RT gradually changed to a red-brown color upon heating to 393 K, and the yellow color can be recovered by cooling the sample. The temperature-dependent UV–vis absorption spectra revealed that the absorption band underwent redshifts with the absorption edge moving from 560 nm at 293 K to 605 nm at 393 K, which agrees well with the observed color change of 1 (Figure S15).…”
Section: Resultsmentioning
confidence: 72%
“…Moreover, the single crystal of 1 shows the thermochromic property that is similar to the other Cu II Cl complexes. ,,, As shown in Figure S14, the yellow single crystal at the RT gradually changed to a red-brown color upon heating to 393 K, and the yellow color can be recovered by cooling the sample. The temperature-dependent UV–vis absorption spectra revealed that the absorption band underwent redshifts with the absorption edge moving from 560 nm at 293 K to 605 nm at 393 K, which agrees well with the observed color change of 1 (Figure S15).…”
Section: Resultsmentioning
confidence: 72%
“…The reliable modulation of photoelectric characteristics in phase-transition materials has been demonstrated due to the diversity of organic and inorganic constituents. [1][2][3][4][5][6][7][8][9][10] An important characteristic of phase-transition materials is their stimulus-response properties such as step-like change of dielectric permittivity in the case of switchable dielectrics, [11][12][13][14][15][16][17][18] onset of ferroelectric order in ferroelectrics, [19][20][21][22][23][24][25][26][27][28] appearance of second-harmonic generation (SHG) in second-order nonlinear optical (NLO) materials, 21,24,25,27,29 and appearance of magnetic order in ferromagnets or antiferromagnets. 26,27,30 These materials can be reversibly switched between different states in the transmission or memory of signals or phase states, when exposed to external stimuli such as light, temperature, pressure or magnetic field, thus showing outstanding potential in multiple fields such as data storage, 31 photoelectric switches, sensors, and data communication-and therefore their physical properties have been widely studied.…”
Section: Introductionmentioning
confidence: 99%
“…45 Further, the lead-free perovskite material (2,5-DCA) 2 CuCl 4 (2,5-DCA = 2,5-dichloroamylaminium) reported by our group exhibits a reversible thermochromic/dielectric response under thermal stimulation. 42 Consequently, there is an urgent need to develop lead-free 2D OIHP materials with reversible thermochromic/dielectric responses.…”
Section: Introductionmentioning
confidence: 99%